Development of an e-health app to support women prescribed adjuvant endocrine therapy after treatment for breast cancer - Brett, Jo (Patient Prefer Adherence, 2018)
BACKGROUND: Adjuvant endocrine therapy (AET) is prescribed to women for 5–10 years after treatment for estrogen receptor positive (ER+ve), early-stage breast cancer. AET has proven effectiveness in reducing the risk of recurrence of breast cancer and mortality. However, adherence is known to be suboptimal with around 20% discontinuing by 2 years and up to 50% discontinuing by 5 years. Interventions are needed to support women taking AET after breast cancer. The aim of this study was to develop and pilot test an e-health app for this population. METHODS: Two focus groups (n=15) and five interviews were conducted with women following treatment for early-stage breast cancer to assess the likely acceptability of an e-health app and to inform the content (Phase I). Following development of a prototype e-health app, a simple heuristic usability test was completed by five women in order to identify any design usability problems (Phase II). A further 18 women used the app for 1 month between July and August 2016, after which they were interviewed by telephone to collect their experiences and views of the app (Phase III). RESULTS: The prototype e-health app included evidence-based information on effectiveness of AET, an electronic side-effects diary, a peer support forum, a repeat prescription reminder, suggested strategies for facilitating adherence and managing any side effects that occur, and a link to further evidence and useful organizations for further information and support. The app was received positively by women. Women found the app useful as it emphasized the importance of taking AET, helped them manage their side effects and provided details of support organizations, while offering empathy and exchange of suggestions for self-management strategies through the peer support forum. CONCLUSION: Overall, findings suggest that this novel e-health app has potential as a feasible medium for promoting adherence to AET. Future research should evaluate the efficacy of the app in supporting women and promoting adherence.